Nephroprotective Effect of Hydroalcoholic Extract Allium jesdianum Boiss against Carbon Tetrachloride Induced Nephrotoxicity via Stress Oxidative in Mice - Heibatolla Kalantari; Maryam Danesh Pajou; Parvin Kheradmand; Maedeh Goodarzian; Leila Zeidooni (Tabriz University of Medical Sciences, 2018)
Background: Nephrotoxicity is one of the most common renal problems that especially occur when the body is exposed to drugs or chemical reagents. Allium jesdianum Boiss is the largest and most important plants genus of onion family that possesses many pharmacological effects. The present study was undertaken to investigate the effect Allium jesdianum Boiss in the treatment of nephrotoxicity induced by carbon tetrachloride (CCl4). Methods: Forty two male mice were randomly divided into six groups; control, sham, CCl4 (1 ml/Kg, i.p) single dose, Allium (500, 1000 and 2000 mg/kg) + CCl4. Blood urea nitrogen (BUN) and serum creatinine (Cr) evaluated in serum. Glutathione (GSH), catalase (CAT), malondialdehyde (MDA) and reactive oxygen species (ROS) were analyzed in kidney tissue homogenate and done the microscopic studies of renal tissue. Results: The results indicated a significant increase of serum BUN and Cr as well as MDA and ROS levels and decrease of GSH and CAT in CCl4 treated mice when compared with the control group (p < 0.001), whereas all studied endpoints were significantly altered in pretreatment with Allium extract when compared with CCl4 treated mice (p < 0.001). Renal histopathology indicated normal appearances reduced in CCl4 treated mice and Allium extract administration improved changes in renal tissue. Conclusion: Administration of the hydroalcoholic extract of Allium jesdianum Boiss could prevent nephrotoxicity induced by CCl4. The protective potential may involve the powerful antioxidant of this plant by eliminating free radicals induced by CCl4.